Role of percutaneous testis biopsy in management of patients with azoospermia - N. G. Gasanov; S. I. Gamidov; T. V. Shatylko; A. Yu. Popova; N. P. Makarova; I. V. Ushakova; O. B. Loran (Исследования и практика в медицине, 2020)
Purpose of the study. To determine the practical value of puncture methods for obtaining spermatozoa in azoospermia. Patients and methods. The results of 127 puncture biopsies of testis (TESA) and testicular appendage (PESA) in patients with azoospermia of presumably obstructive origin were analyzed. The sperm production frequency (SPF) was calculated, as well as the frequency of transition to an open testicular biopsy. Was built a logistic regression model to analyze factors influencing the result, TESA / PESA, which included as independent variables the following parameters: patient age, duration of involuntary infertility, the level of sex hormones (testosterone, estradiol, luteinizing hormone, follicle-stimulating hormone, prolactin, progesterone, inhibin B), the total volume of testes, presence of varicocele, the presence of chemotherapy or radiation therapy, a history of alcohol abuse, Smoking, regular violation of the thermal mode, surgery in the inguinal and scrotal region. Indicators of the probability ratio (PR) with a 95% confidence interval (95% CI) were obtained. Results. 92 biopsy attempts out of 127 were successful, and the NPV was 72.4%. Independent statistically significant predictors of PESA / TESA success were testicular volume (PR = 1.113; 95% CI = 1.026–1.207) and inhibin b level (PR = 1.026; 95% CI = 1.011–1.041). In 35 patients whose spermatozoa were not found during the puncture biopsy, conversion to open microsurgical biopsy was performed. Conclusion. PESA and TESA have only limited effectiveness in azoospermia. We believe that puncture biopsy of the testicles and epididymis is justified only in patients with normal testicular volume and high levels of inhibin B. PESA / TESA should be performed in conditions that allow immediate transition to an open biopsy in case of failure.